Deep brain stimulation as a treatment for Parkinson's disease (Research, Society and Development, 2023)
Introduction: Parkinson's disease (PD) is the second most common neurodegenerative disease and has been increasing in prevalence in recent decades. Deep brain stimulation (DBS) is an established treatment for severe Parkinson's disease (PD), dystonia, and tremor, and has an emerging role in a number of other neurological and neuropsychiatric conditions. However, its widespread adoption is currently limited by cost, side effects, and partial effectiveness. Objective: explain and describe the Deep Brain Stimulation method for the control and treatment of Parkinson's Disease. Search methodology: this is a descriptive research of the integrative literature review type, through online access to the PubMed, Scielo, CDSR, Google Scholar, VHL and EBSCO databases, in September 2021. Results and discussion: DBS can interact with pathological neural networks in a way that sometimes stimulates and sometimes inhibits certain pathways in order to eliminate or subdue the unwanted circuit in the basal ganglia loops, this mechanism became known as “blocking” the diseased network. Controlled stimulation reduces this hyperactivity and consequently removes noise, reestablishing the transmission of neural information and, consequently, returning movement control. Final considerations: the treatment consists of electrical stimulation in different regions of the brain, for years without interruption. The electrical current used is very small, made at strategic points in the brain through the implantation of electrodes, which are, for the most part, deep.